25 YEARS OF THE POLISH SOCIETY FOR STEREOLOGY - Wojnar, Leszek (Image Analysis and Stereology, 2013)
25 years history of the Polish Society for Stereology is summarized by a person playing active role in the Society from the very beginning till now. Formation and growth of the society is described with emphasize to some milestones in the Society history. This paper is the first attempt to summarize the activity of this scientific organization.